Regional income inequalities and public investments in rural India - Seema Bathla; Anjani Kumar; Pramod K Joshi (Agricultural Economics Research Review, 2023)
Regional inequalities in income levels in the agricultural sector have increased over time, but not as sharply as in the non-agricultural sectors. This article examines the effect of public investments on agricultural income inequalities across 17 major Indian states for the period 1981/82 to 2013/14 and for the pre- and post-liberalisation periods. The impact of conventional inputs and various types of public investments on income inequality is found to be significant but spending on education and health have larger adverse effects compared with spending on roads, energy, and irrigation over time. Land, labour, and private investment in irrigation also have only a modest impact. Among various categories of public investments contributing to regional income inequality, the contribution of education is estimated to be 32.2% nationally, and 50.8%, 38.5%, and 29.7%, respectively, in the low, middle, and high per capita income states. Results suggest that public investments should target roads, energy, irrigation, and agricultural research and development in the less-developed, more agriculture-dependent states to improve regional income equality, increase agricultural productivity, and alleviate rural poverty. The marginal returns to each of these investments, in terms of reducing income inequality, are generally higher in the low-income, agriculture-dominant states, implying the potential benefit of a location-specific expenditure policy.